Quadrivalent influenza vaccines in low and middle income countries: Cost-effectiveness, affordability and availability. Issue 28 (27th June 2018) - Hendriks, Jan; Hutubessy, Raymond C.W.; Grohmann, Gary; Torelli, Guido; Friede, Martin; Kieny, Marie-Paule
Abstract: In high-income countries, there is an increased tendency to replace inactivated seasonal trivalent influenza (TIV) vaccines with quadrivalent (QIV) vaccines as these are considered to give a greater public health benefit. In addition, several recent studies from the USA and Europe indicate that replacement with QIV might also be cost-effective; however, the situation in low- and middle-income countries (LMIC) is less clear as few studies have investigated this aspect. The paper by de Boer et al. (2018) describes a dynamic modelling study commissioned by WHO that suggests that in LMICs, under certain conditions, QIV might also be more cost-effective than TIV. In this commentary, we discuss some important aspects that policymakers in LMICs might wish to take into account when considering replacing TIV by QIV. Indeed, from the data presented in the paper by de Boer et al. it can be inferred that replacing QIV for TIV would mean a 25–29% budget increase for seasonal influenza vaccination in South Africa and Vietnam, resulting in an incremental influenza-related health impact reduction of only 7–8% when a 10% symptomatic attack rate is assumed. We argue that national health budget considerations in LMIC might lead decision-makers to choose other investments with higher health impact for a budget equivalent to roughly a quarter of the yearly TIV immunization costs. In addition to an increased annual cost that would be associated with a decision to replace TIV with QIV, there would be an increased pressure on manufacturers to produce QIV in time for the influenza season requiring manufacturers to produce some components of the seasonal vaccine at risk prior to the WHO recommendations for influenza vaccines. Unless the current uncertainties, impracticalities and increased costs associated with QIVs are resolved, TIVs are likely to remain the more attractive option for many LMICs. Each country should establish its context-specific process for decision-making based on national data on disease burden and costs in order to determine whether the health gains out-weigh the additional cost of moving to QIV. For example, immunizing more people in the population, especially those in higher risk groups, with TIV might not only provide better value for money but also deliver better health outcomes in LMICs. Countries with local influenza vaccine manufacturing capacity should include in their seasonal influenza vaccine procurement process an analysis of the pros- and cons- of TIV versus QIV, to ensure both feasibility and sustainability of local manufacturing.